Hou Hanru : On The Mid-Ground - Yu Hsiao-Hwei; Balkema, Annette W.; Davidts, Wouter; Gao, Minglu; Hou, Hanru; Jouanno, Evelyne; Ning, Ou; Obrist, Hans-Ulrich; Sans, Jérôme; Slager, Henk; Thea, Carolee; Vanmeirhaeghe, Tijl (Hong Kong : Timezone 8, 2002)
Ren Jian ; Wang Jianwei ; Shi Yong ; Qian Weikang ; Lin Yilin ; Chen Shaoxiong ; Xu Tan ; Liang Juhui ; Zhan Wang ; Shi Yong ; Geng Jianyi ; Gu Wenda ; Shan Zhuan Wu ; Xu Bing ; Huang Yong Ping ; Xiamen Dada ; Chen Zhen ; Zhang, Peili ; Yang Jiechang ; Yan Pei-Ming ; Cai Guo-Qiang ; Wang Du ; Shen Yuan ; Lin Yilin ; Durham, Jimmie ; Samore, Sam ; Feydjou, Choreh ; Hartoum, Mona ; Ward, Nari ; Zhou Tiehai ; Zhang Yimou ; Hammons, David ; Konrad, Aglaia ; Blocher, Sylvie ; François, Michel ; Geers, Kendell ; Sinclair, Rose ; Zheng Guogu ; Todori, Grazia ; Haaning, Jens ; Kusolwong Surasi ; Suh Do Ho ; Ozawa Tsuyoshi ; Jun 'Ya Yamaide ; Feng Mengbo ; Wang, Junjieh ; Tan, Fiona ; Piper, Keith ; Haraldsson, Arni ; Pau, Ellen ; Yung Ho Chang ; Yin Xiuzhen ; Zhan Wang ; Zhang, Peili ; Zhu Jia ; Liang Juhui ; Chen Shaoxiong ; Song Dong ; Wang Jin ; Yin Xiuzhen ; Zhu Fadong ; Zhao Bandi ; Jodogne, Lucas ; Shen Yuan ; Hirschhorn, Thomas ; Taniuchi, Tsuneko ; Sarkis ; Lévêque, Claude ; Farrell, Seamus ; Shen Yuan ; Yang Jiechang ; Han Myung-Ok ; Abdessemed, Adel ; Benyahia, Samta ; Reinoso, Pablo ; Damag, Gaston ; Ruiz de Infante, Francisco ; Bidjocka, Bili ; Tesi, Alessandra ; Shahrokh Nederi, Ladan ; Nakayama, Jiro ; Solomoukha, Kristina ; Zwelethu ; Rawanchaikul, Navin ; Tiravanija, Rirkrit ; Xu Tan ; Lee, Bul ; Yong Ho Chang ; Koolhaas, Rem ; Liew Kung Yu ; Xu Tan ; Ken Lum ; Bodys Isek Kingelez ; Kawara, On ; Yang Zhenzhong ; Blanckart, Olivier ; Schiess, Adrian ; Buchanan, Roderick ; Renaud, David ; Samore, Sam ; Streuli, Beat ; Bernardini, Alain ; Guaita, Carlo ; Zieger, Brigitte ; Gaba, Meschac ; Gartz, Wineke ; van Houwelingen, Hans ; de Jong, Aletta ; B.a.d. ; MacKenna, Tracy & Janssen Edwin ; De Geuzen
Engels
boek
Keywords: Azië; China